PSIKOLOGI HUMANISTIK ABRAHAM MASLOW DALAM REPRESENTASI PENUTURAN TOKOH ROBOHNYA SURAU KAMI KARYA A. A NAVIS - Putri, Ayu Aprilia; Febriyanti, Thrisa Ayu (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2020)
Short stories are reading material that tells short stories, are interesting, and arouse the emotions of readers. Describe the story of the highlighted figure with fictional cohesiveness. In a short story, the characters are raised and subject to a problem until the completion stage. The purpose of this study is to analyze how the hierarchy of Abraham Maslow's multilevel needs theory, represented by figures in the collection of the storyline Surau Kami by A.A Navis. The object of this study is the short story Surau Kami. This type of research uses descriptive qualitative methods with a psychological psychology approach. Content content analysis model. Use reading techniques and note things related to the purpose of the study. Based on the results of the analysis in the story of Robohya Surau Kami by A.A Navis, it can be concluded that the author has synchronously presented an extraordinary story in the story of Roboh Surau Kami. There are five hierarchical needs of Abraham Maslow's theory, namely: physiological needs represented by the figures Grandfather and Mr. Kari. The needs of love and possessions from the representation of the figures Indra Budiman and Mr. O.M, The need for security is represented by the figures Grandfather and Lena. The need to be respected is represented by Misri and the mother. The highest need is self-actualization represented by a nurse figure. Keywords: Hierarchy of needs, and short stories.